Childhood subject in N. A. Taffy’s creativity (Eurasian Journal of Philology Science and Education, 2016)
In article discusses the features of the topic on the example of childhood stories Russian writer abroad N.A.Teffi. Sets the value of the subject in her work, how to display the reality through the eyes of children in correlation with established traditions in the literature. With biographical and structural semiotic analysis methods discussed stories from the book Taffy 1910–1916–ies, little studied in literary criticism of the twentieth century. The classification of short stories, short stories divided into 3 groups based on 3 age groups and respective stages of formation of the child’s mind. The analysis methods of the topic of childhood, the main result of which should be regarded as a conclusion about the special significance and methods of antithesis oxymoron, irony and satire.
Keywords: childhood; tradition; story; images; title; irony; antithesis; oxymoron.